Arsénico en el agua de rechazo en plantas potabilizadoras de agua subterránea que utilizan la tecnología de ósmosis inversa en la provincia de Santa Fe. Propuestas de gestión para una problemática ambiental - El Kassisse, Yanina (2025)
Arsenic (As) is one of the most toxic inorganic contaminants; it is primarily present in groundwater and has been detected in a wide range of concentrations worldwide. Human exposure to this compound is due to the consumption of water with high As content and the ingestion of foods prepared or cultivated with such water, producing serious health problems. Its presence in groundwater greatly compromises this valuable resource as a safe source of drinking water for humans, which is why its removal must be managed so that the water complies with the limits established in the Argentine Food Code (AFC). In our country, reverse osmosis (RO) is one of the most widely used technologies to remove As from groundwater. This method removes it from raw water and concentrates it in wastewater streams called reject water, which must be properly managed, as improper disposal can generate environmental problems, altering the water quality of the receiving body and causing negative impacts on aquatic life. Considering this, the general objective of this thesis was to develop and propose to the authorities of Aguas Santafesinas (ASSA) management recommendations for the reject water stream according to the concentration of As in both the reject water and the raw water, in groundwater treatment plants that use RO technology. To this end, samples of raw water, reject water, and permeate water were collected from the treatment plants operated by ASSA in the towns of Cañada de Gomez, Firmat, Galvez, Rafaela, and Rufino, which use RO technology and groundwater as a source, and As content was determined. The concentration of As in the permeate water of all treatment plants analyzed was always non-detectable (detection limit of 2 µg/L). As concentration in reject water ranged from 34 ?g/L to 128 ?g/L, complying with the limit of 500 ?g/L. As concentration in raw water ranged from 10 to 50 ?g/L, values that were lower than those reported in the literature for this area. Based on the results obtained in this study and those periodically monitored by ASSA, As concentrations in reject water do not appear to pose an environmental risk, since they comply with current regulations. For this reason, plants dispose of reject water according to their convenience, either by discharging it into sewage systems or into receiving bodies of water. Nevertheless, recommendations for its disposal, such as the use of phytotechnologies (biosorption and constructed wetlands), have been proposed, in order to further reduce the environmental impact of As, since these methods allow the removal of this contaminant from reject water.